Fabulae and Imaginatio in Gianfrancesco Pico’s Thought - Pappalardo, Lucia (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2019)
In Renaissance philosophy, the term fabula is often used to mean a poetic or fantastic tale that conceals the truth beneath metaphorical language. This article will focus on a rather different concept of fabula found in Gianfrancesco Pico della Mirandola’s works. To the younger Pico, the entire tradition of Greek and Latin poetry is a fabula: that is, a false and immoral narration inspired by demons. In the first part of this article, I will trace the origin of this use of fabula to the early Christian apologists. I will argue that Gianfrancesco’s intention was to build on this idea through an interpretation of ancient thought that differed from the historiographical model of prisca theologia proposed by Marsilio Ficino and Giovanni Pico. In the second part, I will show the close relationship, in Gianfrancesco’s philosophy, between fabula and imaginatio.